Circulating miRNA-21 as early potential diagnostic biomarker for acute myocardial infarction: a meta-analysis - Wang, Ke; Li, Kai; Li, Zhuoyuan; Yan, Xizhang (Frontiers in Cardiovascular Medicine, 2024)
There exists a knowledge gap concerning the clinical significance of miRNA-21; therefore, in the present study, we aimed to estimate the diagnostic and prognostic accuracy and sensitivity of miRNA-21 in acute myocardial infarction (AMI) by performing an evidence-based meta-analysis of previous AMI-related clinical studies. Chinese and English literature published before April 2024 were searched, and data were reviewed and extracted. After quality appraisal, the STATA 16.0 software was used for the effect size analysis of the various treatments described in the literature. A total of 14 valid documents were retrieved from 562 studies. The results of the systematic review revealed that for the patients with AMI vs those without non-AMI, the aggregated odds ratio reached 5.37 (95% confidence interval 3.70-7.04). The general sensitivity and specificity for the circulating miRNA-21 levels in diagnosing AMI were 0.83 and 0.81, respectively. Thus, the meta-analysis of 14 AMI-related clinical trials highlighted that miRNA-21 may serve as a promising biomarker for diagnosing AMI.